Respuesta :
Multiply the fraction by the (denominator/denominator)
Which is equals to 1.
1/root3-1 * (1/root3-1) / (1/root3-1)
Now you have root3-1 / 2
Which is equals to 1.
1/root3-1 * (1/root3-1) / (1/root3-1)
Now you have root3-1 / 2
Solution:
[tex] \frac{1}{ \sqrt{3} - 1 } \\ = \frac{1}{ \sqrt{3} - 1} \times \frac{ \sqrt{3} + 1}{ \sqrt{3} + 1 } \\ = \frac{ \sqrt{3} + 1}{( \sqrt{3})^{2} - (1)^{2} } \\ = \frac{ \sqrt{3} + 1 }{3 - 1} \\ = \frac{ \sqrt{3} + 1}{2} [/tex]
Answer:
[tex] \frac{ \sqrt{3} + 1}{2} [/tex]